Caribbean Common Market trade policies and regional integration in the 1990s (World Bank New YorkUS, 1990)
Provides an overview of the economic structure and performance of CARICOM. Analyses the different features of the current trade policy regime and their impact on trade patterns and performance. Discusses regional and national aspects of the industrial policy regime. Describes the policy regime and institutional framework for agriculture and assesses the effectiveness of regional cooperation in the area of monetary and payments policies. Reviews current reform programmes at the national and regional level.
DC